Batasan Kewenangan Otoritas Jasa Keuangan Terhadap Lembaga Keuangan Mikro Berbentuk Badan Hukum Koperasi Simpan Pinjam dalam Hal Terjadi Gagal Bayar: Limitations of the Financial Services Authority's Authority on Microfinance Institutions in the Form of Savings and Loans Cooperative Legal Entities in the Event of Default - Tobing, Dwinoven Lumban; Dewantara, Reka; Wicaksono, Setiawan (WARKAT, 2022)
The rapidly increasing growth of the Indonesian economy has influenced the monetary system in State Financial Institutions, especially institutions operating in the financial services sector which provide services to the public in collecting funds. The independent institution that is responsible for providing supervision and regulation in the financial services sector is the Financial Services Authority so that this regulation will be discussed by the author in his research regarding the Limits of the Financial Services Authority's Authority on Microfinance Institutions in the Form of Cooperative Legal Entities in the Event of Default and whether the OJK can provide legal protection in overcoming these problems as an independent institution operating in the financial services sector. This research is normative juridical legal research by examining and approaching various legal rules that regulate the existence of regulations regarding the authority possessed by the OJK using a case approach that occurred in the Indosurya Cipta Savings and Loans Cooperative which experienced a state of default. OJK has the authority to grant business permits to MFIs before carrying out their business activities and carry out guidance, regulation and supervision of MFIs as contained in the provisions of Law Number 1 of 2013 concerning Microfinance Institutions. This regulation gives authority to the OJK in licensing, regulating and supervising MFIs where the establishment of an MFI with a Cooperative legal entity consists of establishing and ratifying a Cooperative legal entity by the Ministry of Cooperatives and Small and Medium Enterprises as well as submitting an MFI business application to the OJK. OJK's authority over MFIs in the form of cooperative legal entities is in line with the system of delegation of authority by the Ministry of Cooperatives and SMEs, Regency/City Regional Governments, and OJK.